PENGARUH INTEGRASI FLIPPED CLASSROOM DENGAN PROBLEM BASED LEARNING BERBANTUAN ANIMASI TERHADAP HASIL BELAJAR KOGNITIF SISWA - Humairah, Saidatul; Syafrizal, Syafrizal; Safriana, Safriana; Sakdiah, Halimatus; Novita, Nanda (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research aims to determine the effect of a flipped classroom integrated with animation-assisted Problem Based Learning on students' cognitive learning outcomes in thermodynamics material at SMA Negeri 1 Gandapura. The type of research used was quasi-experimental with a design in the form of a nonequivalent control group design. The sampling technique used was purposive sampling, with a population of all class XI IPAS students. The sample in this research was class XI Science 3 as an experimental class taught using a flipped classroom integrated with Problem Based Learning assisted by animation and class The research instrument is the test. validation test of 20 questions that have been validated by experts using SPSS software. The results of data testing using the independent sample t test obtained a sig value. (2-tailed) of 0.000 < 0.05. From this test it can be concluded that the flipped classroom model integrated with problem based learning assisted by animation has an effect in improving students' cognitive learning outcomes compared to conventional models